Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/ic302790m
|View full text |Cite
|
Sign up to set email alerts
|

Robust Dirac-Cone Band Structure in the Molecular Kagome Compound (EDT-TTF-CONH2)6[Re6Se8(CN)6]

Abstract: (EDT-TTF-CONH2)6[Re6Se8(CN)6] is a molecular solid with R3 space group symmetry and has the remarkable feature of exhibiting hybrid donor layers with a kagome topology which sustain metallic conductivity. We report a detailed study of the structural evolution of the system as a function of temperature and pressure. This rhombohedral phase is maintained on cooling down to 220 K or up to 0.7 GPa pressure, beyond which a symmetry-breaking transition to a triclinic P1 phase drives a metal to insulator transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Octahedral rhenium cluster complexes due to their antitumoral, antibacterial, photoluminescent, redox, and X-ray contrast properties are appealing inorganic species for applications in biology and medicine. Their encapsulation within biocompatible drug carrier, such as cyclodextrins, represents a promising way to develop biological applications. In context, we demonstrated that clusters [Re 6 Q 8 (CN) 6 ] 4– (with Q = S, Se, and Te; see Figure a–c) interact with γ-CD, forming strong host–guest complexes built on cluster embedded within two tori hosts …”
Section: Introductionmentioning
confidence: 99%
“…Octahedral rhenium cluster complexes due to their antitumoral, antibacterial, photoluminescent, redox, and X-ray contrast properties are appealing inorganic species for applications in biology and medicine. Their encapsulation within biocompatible drug carrier, such as cyclodextrins, represents a promising way to develop biological applications. In context, we demonstrated that clusters [Re 6 Q 8 (CN) 6 ] 4– (with Q = S, Se, and Te; see Figure a–c) interact with γ-CD, forming strong host–guest complexes built on cluster embedded within two tori hosts …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focused on the luminescent and electrochemical properties of the molecular [Re 6 Se 8 ] 2+ unit, as well as using the cluster core as a building block to prepare materials for a variety of applications. This investigation focuses on Re 6 Se 8 Cl 2 with the [Re 6 Se 8 ] 2+ cluster unit isostructural to that found in the superconducting Mo 6 Q 8 Chevrel-phase core . Theoretical and experimental studies have explored the ability of Chevrel-phase materials (Mo 6 S 8 ) to reversibly transfer four electron equivalents (ee) per formula unit. Unlike the molybdenum analogue, the hexarhenium core has been studied as a “building unit” in extended solid frameworks, where motifs of three, two, and one dimensionality are possible. , These frameworks consist of rigid cluster–cluster linkages, some of which can undergo dimensional reduction in the presence of Cs + or Tl + halides.…”
mentioning
confidence: 99%
“…Consequently, if the coupling through donors B could be reinforced, for instance through applied pressure, and the metallic state could be stabilized, the Fermi level would occur at the K point and thus would coincide with a Dirac cone which could lead to the exotic transport properties predicted for this situation. 35 Among molecular conductors, only (EDT-TTF-CONH 2 ) 6 [Re 6 Se 8 (CN) 6 ], 36,37 a-(BEDT-TTF) 2 I 3 under pressure, 38 [Pd(dddt) 2 ] (dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate) under pressure, 39 [Pt(dmdt) 2 ] (dmdt = dimethyl-tetrathiafulvalenedithiolate) 40 and, very recently, a-(BETS) 2 I 3 (BETS = bis (ethylenedithio)-tetraselenafulvalene) 41 have been previously shown to exhibit such an uncommon electronic feature. Unfortunately, our measurements suggest that in the present salts the electrons remain localized at the pressures we could reach.…”
Section: Synthesis and Structure Of The Radical Cation Saltsmentioning
confidence: 99%